2003
DOI: 10.1093/carcin/bgg184
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanidins inhibit activator protein 1 activity and cell transformation: structure-activity relationship and molecular mechanisms

Abstract: Anthocyanins are the chemical components that give the intense color to many fruits and vegetables, such as blueberries, red cabbages and purple sweet potatoes. Extensive studies have indicated that anthocyanins have strong antioxidant activities. To investigate the mechanism of anthocyanidins as an anticancer food source, six kinds of anthocyanidins representing the aglycons of most anthocyanins, were used to examine their effects on tumor promotion in mouse JB6 cells, a validated model for screening cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(144 citation statements)
references
References 58 publications
7
130
2
5
Order By: Relevance
“…Meiers et al (2001) reported that cyanidin and delphinidin inhibited the tyrosine kinase activity of the epidermal growth-factor receptor. Hou et al (2004) reported that delphinidin, petunidin and cyanidin inhibited the activity of transcription factor activator protein 1 (AP-1), which is stimulated by oxidative stress, and they also reported that delphinidin and cyanidin inhibited cyclooxygenase-2 (COX-2) expression in lipopolysaccharide (LPS)-activated macrophage cells (Hou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Meiers et al (2001) reported that cyanidin and delphinidin inhibited the tyrosine kinase activity of the epidermal growth-factor receptor. Hou et al (2004) reported that delphinidin, petunidin and cyanidin inhibited the activity of transcription factor activator protein 1 (AP-1), which is stimulated by oxidative stress, and they also reported that delphinidin and cyanidin inhibited cyclooxygenase-2 (COX-2) expression in lipopolysaccharide (LPS)-activated macrophage cells (Hou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent observations also suggest that ellagitannin, a constituent of Jamun and its colonic 3 Gallic acid 1) Inhibits the TPA-induced inductions of epidermal ornithine decarboxylase activity, hydroperoxide production and DNA synthesis, and also inhibit the promotion of skin papillomas and carcinomas in the two-step initiationpromotion protocol [79]; 2) Administering (0.3% to 1%) for twenty consecutive weeks from four weeks of age to the male TRAMP mice (a transgenic mice develops prostate tumor) caused a decrease tumors with decreasing the proliferative index with a concomitant increase in the apoptotic cells which were due to decrease in the expression of Cdc2, Cdk2, Cdk4, Cdk6, cyclin B1 and E [83]. [91,92], and mitogen-activated protein kinase (MEK) [93] and inhibitor of of neoplastic cell transformation and MEK1 [94]; 2) Prevents TPA-induced transformation, PKC activation, and c-jun expression in mouse fibroblast cells [95]; 3) Suppresses UVB-induced skin cancer by targeting Fyn in JB6 cells [96]. Inhibits Akt survival signaling and induces Bad-mediated apoptosis in immortalized human keratinocytes (HaCaT cells) [97]; 4) Inhibits matrix metalloproteinase 2 protein expression and enzyme activity in colorectal carcinoma cells [98] and also down-regulates phorbol ester-induced cyclooxygenase-2 expression in mouse epidermal cells by blocking activation of nuclear factor kappa B [94]; 5) Inhibits polycyclic aromatic hydrocarbon-DNA adduct formation in epidermis and lungs of SENCAR mice [99].…”
Section: Chemopreventive Effectsmentioning
confidence: 99%
“…16 It has also been suggested that anthocyanins may indirectly reduce oxidative stress by activating specific detoxification enzymes such as glutathione reductase, glutathione peroxidase, glutathione S-transferase and quinone oxidoreductase. 17 At cellular level, anthocyanins produce different effects: they inhibit tumorigenesis by blocking activation of a mitogen-activated protein kinase pathway, 18 reduce estrogenic activity, induce cytokine production and decrease capillary permeability, 19 whereas when administered to adipocytes, anthocyanins exert a protective role against H 2 O 2 or tumor necrosis factor-a-induced insulin resistance. 20 Interestingly, two of these processes, oxidative stress and regulation of insulin signalling, are both involved in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%